A study of the Malaysian youth perception toward 'Muslim Pro' apps through smart phone in Malaysia using technology acceptance model (TAM) / Hafizah Rosli and Ruslan Abd Rahim - Rosli, Hafizah; Abd Rahim, Ruslan (2016)
The justification of this exploratory study is to get a better understanding on current situation of the Malaysian youth perception toward 'Muslim Pro' apps through their smartphones. Moreover, most of previous studies focused on the categories and types of mobile applications but not specific on the consumers' perception (Heidi, 2014) Thus, the purpose of this study is to identify the users perception, use and usefulness of the mobile app that give a certain impact toward improving their practice toward basic Islamic principle as Muslim in Malaysia. Additionally, the user's perception as Muslim through this religion application had been examined through online survey by using The Technology Acceptance Model (TAM) as variable to measure. As conclusion, this information is beneficial for academics for the development of future research in the field as to improved future propose mobile application toward our Muslim society in Malaysia.